Revenue Diversification in Housing Nonprofits: Impact of State Funding Environments. (June 2016) - Shea, Jennifer; Wang, Janey Qian
Scholars often draw on resource dependence theory and institutional theory to explain nonprofit behavior in light of resource constraints, but few studies include empirical indicators of environmental constraints. This study examines the degree to which variables in the state-level funding environment promote (or deter) revenue diversification for housing nonprofits. It uses a hierarchical linear model (HLM) to capture constraint at two levels: the funding environment at the state level and organizational-level factors. Analyzing data from 990 housing nonprofits in 26 states and public funding environment variables for each of those states from 2008 to 2010, we find that state funding has a negative impact on revenue diversification for housing nonprofits. By including empirical indicators of the level of constraint for specific funding sources, we add to the body of literature that questions normative nonprofit financial management and provide evidence nonprofit leaders can use to inform their resource development strategies.